2016
DOI: 10.1038/srep29420
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous water supply affects growth and benefits of clonal integration between co-existing invasive and native Hydrocotyle species

Abstract: Spatial patchiness and temporal variability in water availability are common in nature under global climate change, which can remarkably influence adaptive responses of clonal plants, i.e. clonal integration (translocating resources between connected ramets). However, little is known about the effects of spatial patchiness and temporal heterogeneity in water on growth and clonal integration between congeneric invasive and native Hydrocotyle species. In a greenhouse experiment, we subjected severed or no severe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 35 publications
(98 reference statements)
0
7
0
Order By: Relevance
“…It is adaptable to various climatic conditions and can survive both on dry land as well as in places accumulated with water bodies. In many regions of the world, the plant is considered as an invasive weed, which grows in lawns, boggy areas and on the banks of small rivers and rivulets (Wang et al, 2016).…”
Section: Botanymentioning
confidence: 99%
See 1 more Smart Citation
“…It is adaptable to various climatic conditions and can survive both on dry land as well as in places accumulated with water bodies. In many regions of the world, the plant is considered as an invasive weed, which grows in lawns, boggy areas and on the banks of small rivers and rivulets (Wang et al, 2016).…”
Section: Botanymentioning
confidence: 99%
“…The propagation of the plant is feasible either by sexual or vegetative methods. The plant reproduces either from its seeds or from the sprout that grows from the creeping stems (Wang et al, 2016). The plant requires full sunlight for its optimum growth.…”
Section: Botanymentioning
confidence: 99%
“…Clonal integration helped clonal plants exploit ubiquitous heterogeneous resources, improve the growth performance of the whole genet and occupy new habitats [15][16][17]. Extensive studies have been reported on the role of clonal integration in coping with heterogeneous resources, such as water, nutrients, light, space and others for clonal plants [17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Most studies used pairs of mother ramet and daughter ramets subjected to homogeneous and heterogeneous water and nutrient treatments as materials. The translocation and sharing patterns of water and nutrients, as well as the photochemical activities and growth performances of mother and daughter ramets, were well documented [17,20,21,27,28]. However, only a few studies were conducted on plot and patch levels to investigate the growth, phenotypic responses and recovery mechanisms of clonal plants to scale-dependent nutrient heterogeneity [22,29,30].…”
Section: Introductionmentioning
confidence: 99%
“…In nature, environmental conditions are usually spatially heterogeneous (Glover et al ; Wang et al ). One potential benefit of clonality is that ramets, connected by belowground rhizomes or aboveground stolons, can share resources and signals, thereby increasing the growth and competition of clonal plants in numerous environments with heterogeneous distribution of light, water, nutrients and competitors (Stuefer et al ; Yu et al ; Song et al ; You et al ; Roiloa et al ; Wang et al ). One type of heterogeneous environment is that some patches favourable for plant growth are interspersed with others that are not favourable for plant growth.…”
Section: Introductionmentioning
confidence: 99%